# Show that the sum of an arithmetic series whose first term is a, second term b and the last is c is equal to

First term = a

Common difference = (b–a)

Last term = c

c = a + (n–1)(b–a)

(n–1) = (c–a) / (b–a)

n = (b + c 2a) /( b – a)

Sum of terms =

Sum of terms =

Hence proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Interactive Quiz:Euclid's Division Lemma44 mins
Fundamental Theorem of Arithmetic-238 mins
Champ Quiz | Fundamental Principle Of Arithmetic41 mins
Fundamental Theorem of Arithmetic- 143 mins
Euclids Division Lemma49 mins
Quiz | Imp Qs on Real Numbers37 mins
NCERT | Imp. Qs. on Rational and Irrational Numbers44 mins
Relation Between LCM , HCF and Numbers46 mins
Application of Euclids Division Lemma50 mins
Quiz | Fun with Fundamental Theorem of Arithmetic51 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses